Effects of exogenous thymosin β4 on carbon tetrachloride-induced liver injury and fibrosis - Xiankui Li (Nature Portfolio, 2017)
Abstract The present study investigated the effects of exogenous thymosin β4 (TB4) on carbon tetrachloride (CCl4)-induced acute liver injury and fibrosis in rodent animals. Results showed that both in mice and rats CCl4 rendered significant increases in serum alanine aminotransferase and aspartate aminotransferase, hepatic malondialdehyde formation, decreases in antioxidants including superoxide dismutase and glutathione, and up-regulated expressions of transforming growth factor-β1, α-smooth muscle actin, tumor necrosis factor-α and interleukin-1β in the liver tissues. Hydroxyproline contents in the rat livers were increased by CCl4. Histopathological examinations indicated that CCl4 induced extensive necrosis in mice livers and pseudo-lobule formations, collagen deposition in rats livers. However, all these changes in mice and rats were significantly attenuated by exogenous TB4 treatment. Furthermore, up-regulations of nuclear factor-κB p65 protein expression by CCl4 treatment in mice and rats livers were also remarkably reduced by exogenous TB4 administration. Taken together, findings in this study suggested that exogenous TB4 might prevent CCl4-induced acute liver injury and subsequent fibrosis through alleviating oxidative stress and inflammation.